'Dieback' (chronic decline) of Eucalyptus viminalis on the Monaro is not new, unique or difficult to explain. Issue 4 (1st October 2016) - Jurskis, V.
ABSTRACT: Ross and Brack (2015) reported a widespread decline over the past decade in the health of Eucalyptus viminalis on the Monaro Tablelands in southern New South Wales. They were unable to attribute this to changes in management, lack of fire, or 'declining levels of structural diversity'. They noted consistent infestation of trees by a native weevil and recommended further work on the role of climate and rainfall in 'Monaro dieback'. However, chronic decline involving a wide range of arbivores has affected a wide range of eucalypts across Australia since European settlement, and is currently rampant in many areas of forest and woodland. Pasture improvement and/or exclusion of fire and grazing are the major causes of chronically declining health of eucalypts. The data presented by Ross and Brack (2015) provide some support for this conclusion and no contrary evidence.